Answer:
x = -3, y = -1
Explanation:
Solve by substitution:
First make the second equation in terms of y:
y = -x-4
Next, since we found what y is, plug it into the first equation and solve for x:
-3x + 5(-x-4) = 4 Plug in
-3x - 5x - 20 = 4 Distribute
-8x - 20 = 4 Simplify
-8x = 24
x = -3
We have found that x = -3. To find y we need to plug x back into any of the equations. Let's do equation #2.
(-3) + y = -4 Plug in
y = -1 Simplify
So, y = -1 and x = -3. Let's check this in the first equation to make sure it is correct:
-3(-3)+ 5(-1) = 4 Plug in
9 + (-5) = 4 Simplify
9 - 5 = 4
4 = 4
Since both sides are equal that means we are correct!
Hope this helps!!